Analisis Yuridis Ketersediaan Sarana Pembuangan Sampah Dengan Perilaku Membuang Sampah Rumah Tangga Di Wilayah Kerja Puskesmas Sitopeng Kota Cirebon Tahun 2023 - Kamasturyani, Yani; Aryanti, Devita (Jurnal Kesehatan Mahardika, 2023)
Garbage is one of the environmental problems that has become a national and even global problem, not just local. The work area of ​​the Sitopeng Health Center is a Health Center located in the Argasun Sub-District where transportation facilities are available, but such as garbage carts, as well as garbage disposal sites at each house are neglected, as are trash containers or trash cans which are recommended by the government for every house in the Kelurahan as a means of waste disposal where every household is still lacking because not all have. This study aims to the behavior of disposing of household waste in the working area of ​​the Sitopeng Health Center, Cirebon City. The research design used was a survey with a cross sectional approach. The instrument used is a questionnaire. The number of samples in this study were 98 respondent.. The sampling technique is simple random sampling using univariate analysis and bivariate analysis with the chi square test. From the results of statistical tests using the chi square test, P Value = 0.001 (< (0.05)) which means that Ho is rejected or Ha is accepted, indicating that there is a significant relationship between the availability of waste disposal facilities and the behavior of disposing of household waste in the working area of ​​the Sitopeng Health Center.Everyone is obliged to reduce waste and handle waste. The mandate of this regulation must be socialized continuously by stakeholders at various levels of government, to make the public aware of the importance of managing household waste to maintain environmental health.It is hoped that the results of this research can encourage increased procurement of waste disposal facilities that can maximize household waste management.